Only if you're lucky eaudiobook A novel. - Willingham, Stacy (Macmillan Audio, 2024)
"Reader Vacker does a remarkable job.... Mystery and true crime fans will be drawn in and ultimately satisfied by this complex, tense tale read expertly by a talented narrator." — Booklist on All the Dangerous Things A sharp and twisty exploration of female friendship from the New York Times bestselling author of A Flicker in the Dark and All the Dangerous Things. Lucy Sharpe is larger than life. Magnetic, addictive. Bold and dangerous. Especially for Margot, who meets Lucy at the end of their freshman year at a liberal arts college in South Carolina. Margot is the shy one, the careful one, always the sidekick and never the center of attention. But when Lucy singles her out at the end of the year, a year Margot spent studying and playing it safe, and asks her to room together, something in Margot can't say no—something daring, or starved, or maybe even envious. And so Margot finds herself living in an off-campus house with three other girls, Lucy, the ringleader; Sloane, the sarcastic one; and Nicole, the nice one, the three of them opposites but also deeply intertwined. It's a year that finds Margot finally coming out of the shell she's been in since the end of high school, when her best friend Eliza died three weeks after graduation. Margot and Lucy have become the closest of friends, but by the middle of their sophomore year, one of the fraternity boys from the house next door has been brutally murdered... and Lucy Sharpe is missing without a trace. From the author of A Flicker in the Dark and All the Dangerous Things comes a tantalizing thriller about the nature of friendship and belonging, about loyalty, envy, and betrayal—another gripping novel from an author quickly becoming the gold standard in psychological suspense. A Macmillan Audio production from Minotaur Books.